Fission Yeast HMT1 Lowers Seed Cadmium through Phytochelatin-Dependent Vacuolar Sequestration in Arabidopsis(1)([C])([W]) - Huang, Jing (American Society of Plant Biologists, 2012)
Much of our dietary uptake of heavy metals is through the consumption of plants. A long-sought strategy to reduce chronic exposure to heavy metals is to develop plant varieties with reduced accumulation in edible tissues. Here, we describe that the fission yeast (Schizosaccharomyces pombe) phytochelatin (PC)-cadmium (Cd) transporter SpHMT1 produced in Arabidopsis (Arabidopsis thaliana) was localized to tonoplast, and enhanced tolerance to and accumulation of Cd(2+), copper, arsenic, and zinc. The action of SpHMT1 requires PC substrates, and failed to confer Cd(2+) tolerance and accumulation when glutathione and PC synthesis was blocked by l-buthionine sulfoximine, or only PC synthesis is blocked in the cad1-3 mutant, which is deficient in PC synthase. SpHMT1 expression enhanced vacuolar Cd(2+) accumulation in wild-type Columbia-0, but not in cad1-3, where only approximately 35% of the Cd(2+) in protoplasts was localized in vacuoles, in contrast to the near 100% found in wild-type vacuoles and approximately 25% in those of cad2-1 that synthesizes very low amounts of glutathione and PCs. Interestingly, constitutive SpHMT1 expression delayed root-to-shoot metal transport, and root-targeted expression confirmed that roots can serve as a sink to reduce metal contents in shoots and seeds. These findings suggest that SpHMT1 function requires PCs in Arabidopsis, and it is feasible to promote food safety by engineering plants using SpHMT1 to decrease metal accumulation in edible tissues.